Revisiting the Interlink between Artificial Intelligence, Market Competition, and Consumer Behaviour - Gunawan, William Ben (JAMI: Jurnal Ahli Muda Indonesia, 2025)
Backgrounds. Artificial Intelligence (AI) has emerged as a transformative force in modern business, influencing competitive dynamics and reshaping consumer behavior. As AI applications expand across industries, understanding their strategic impact on market competition and consumer engagement becomes increasingly vital for business sustainability and innovation. Methods. This study employs a mixed-method approach combining bibliometric analysis and systematic literature review to examine the interrelationship between AI, market competition, and consumer behaviour. Bibliometric analysis was conducted using the Scopus database for the period 2015–2025, with VOSviewer utilized to map keyword co-occurrences and thematic clusters. Subsequently, a qualitative literature review was performed on thematically relevant and highly cited articles to extract insights on AI’s practical implementations, competitive implications, consumer analytics, and ethical concerns. Results. The findings reveal a marked increase in scholarly attention to AI-driven business strategies, particularly between 2023 and 2024. AI is shown to influence market competition by enhancing operational efficiency, fostering innovation, supporting data-driven decision-making, and improving strategic adaptability. In terms of consumer behaviour, AI enables pattern recognition, real-time responsiveness, personalized marketing, and demand forecasting, contributing to customer satisfaction and loyalty. Additionally, AI-powered business operations—such as dynamic pricing and product recommendation systems—further optimize performance. However, ethical challenges, including data privacy, algorithmic bias, and regulatory gaps, underscore the need for responsible AI adoption. Conclusions. AI serves as both a technological enabler and strategic asset in contemporary business ecosystems. Its influence extends beyond automation, offering firms competitive advantage through improved agility and consumer-centered strategies. To fully leverage AI’s potential, businesses must balance innovation with ethical considerations, ensuring transparent governance and human oversight in AI integration.